Kabayanan bahay manggagawa, a transient architecture solution for the industrial workers of Meycauayan Sterling Industrial Park - Lim, Hannah Justine T. (College of Architecture, University of the Philippines Diliman, 2023)
The workers in industrial zones and areas are often compelled to endure poor living conditions to accommodate the nature of their work, and this in turn hinders the acquiring of a skilled labor force for the companies operating in these areas. There is then a need to provide for and improve the living conditions of industrial spaces, as these impact the employing and training environments of these workers as well as their overall wellbeing. A separate establishment whose main purpose is to provide for its employees has yet to be accomplished in the country’s industrial areas. This lack presents an opportunity for their necessities to converge in a space that replenishes them physically, mentally, and emotionally, as well as provide them room to grow in their monotonous work-centric environment. This project will address the underutilization of industrial spaces as large areas that have the potential to be mixed-use and more human-centered. It takes place in Meycauayan City and focuses on Sterling Industrial Park, a compound where several companies’ warehouses are based. It has a demographic of over a thousand employees of both blue- and white-collar professions in each of its five phases. The modernization of some traditional building techniques and familiar industrial forms is aimed to create a bayan or community for these workers. Shipping container vans were utilized to create space modules, offering a more flexible and personal approach to temporary worker housing. Taking inspiration from the main features of the bahay kubo, the project aims to give the workers their own spaces and create tight-knit clusters like the streets of a small village. The facility advocates for the uplifting of these industrial workers, providing a unifying space that conforms to their transient nature and varied needs, and giving them a space that they can call their own bayan.